Revisiting metropolitan house price-income relationships - Oikarinen Elias; Bourassa Steven C.; Hoesli Martin; Engblom Janne (Elsevier (Commercial Publisher), 2025)
We explore long-term patterns of the house price-income relationship across the 70 largest U.S. metropolitan areas. In line with a standard spatial equilibrium model, our empirical findings indicate that regional house price-income ratios are typically not stable, even over the long run. In contrast, panel regression models that relate house prices to aggregate personal income and allow for regional heterogeneity yield stationary long-term relationships in most areas. The house price-income relationship varies significantly across locations, underscoring the importance of using estimation techniques that allow for spatial heterogeneity. The substantial regional differences are closely related to the elasticity of housing supply.